The “Sins” of American foreign policy illustrated in the North Korean nuclear crisis - Jervis, David (Asia in World Politics: Past, Present, and Future, 2021)
This study applies four alleged “sins” of American foreign policy – ignorance, lack of empathy, quick resort to military action, and arrogance – to America’s failed policy regarding the North Korean nuclear program. While that failure cannot be attributed directly to the sins, there is evidence that an approach not characterized by them might lead to better results.